Physicochemical composition of white table wines produced in the Planalto Norte Catarinense, 2020 vintage (Research, Society and Development, 2022)
Although there are grape and table wine producers in the Planalto Norte region of Santa Catarina, analyzes of the physicochemical composition of the products are not carried out by the producers. In this context, the objective of this work is to carry out the physical-chemical characterization of wines produced in the Planalto Norte Santa Catarina, verifying whether table wines produced in the region meet the physical-chemical standards required by current national legislation. The white table wines were collected from eight winemakers, these being samples from the 2020 harvest. The physical-chemical analyzes were carried out in September 2020, at the Physical-chemical Analysis Laboratory of the Federal Institute of Santa Catarina –Canoinhas. The variables evaluated were: relative density, total acidity, soluble solids, pH and wine color. The soluble solids variable had an average value of 6.6 ºBrix. The mean value for relative density was 0.990. Values for the total acidity variable had mean values of 74.3 meq L-1. The mean value for pH was 3.04 for the samples, with a range of values of 2.93 and 3.30. Values for the variable color of wines (Abs 520 nm) had an average value of 0.740. The results of the physicochemical analyzes are in accordance with indices indicated in the literature and in the current Brazilian legislation, and the physicochemical analyzes of wines produced in the Planalto Norte region of Santa Catarina must be carried out at each harvest, in order to monitor the evolution of the quality of wines produced in the region, as well as verifying if they present the minimum quality standards required by current Brazilian legislation.